2012
DOI: 10.1002/jssc.201200636
|View full text |Cite
|
Sign up to set email alerts
|

Chiral determination of a novel acaricide cyflumetofen enantiomers in cucumber, tomato, and apple by HPLC

Abstract: A simple chiral analytical method was developed for the enantiomeric determination of cyflumetofen in cucumber, tomato, and apple by normal-phase HPLC. The effects of mobile phase composition and column temperature on the enantioseparation were evaluated. Excellent separation was achieved at 25°C on a Chiralpak AD-H column, with a mixture of n-hexane and 2-propanol (95:5, v/v) as mobile phase at a flow rate of 1.0 mL/min detecting at 234 nm. The resolution of cyflumetofen enantiomers was up to 5.5. The elution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The separation factor (α) decreased as the proportion of 2‐propanol increased, likely due to the high viscosity of 2‐propanol. The results are similar to those reported by Chen . CO 2 /isopropanol (96.5:3.5, v/v) was chosen as the mobile phase due to the good resolution (3.06) and short retention time (3.11, 3.63 min) obtained using these compounds.…”
Section: Optimization Of Enantioseparation Conditionssupporting
confidence: 84%
See 2 more Smart Citations
“…The separation factor (α) decreased as the proportion of 2‐propanol increased, likely due to the high viscosity of 2‐propanol. The results are similar to those reported by Chen . CO 2 /isopropanol (96.5:3.5, v/v) was chosen as the mobile phase due to the good resolution (3.06) and short retention time (3.11, 3.63 min) obtained using these compounds.…”
Section: Optimization Of Enantioseparation Conditionssupporting
confidence: 84%
“…The other columns were insufficiently able to discriminate between the cyflumetofen stereoisomers. Previous research also found that cyflumetofen is well separated on a coated‐type amylose stationary phase column using HPLC .…”
Section: Optimization Of Enantioseparation Conditionsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, a Joint FAO/WHO Meeting found that cyflumetofen is potentially carcinogenic in male rats (FAO/WHO 2006). Some researchers have reported analytical methods for cyflumetofen (Chen et al 2013;Li et al 2013) and toxicity assessments (Takahashi et al 2012), but few studies have focused on the concentration change during food processing. There are no MRLs for the related processed commodities.…”
Section: Introductionmentioning
confidence: 99%
“…Cyflumetofen is a novel type of benzoyl acetonitrile acaricide developed by Ostuka AgriTechno Co., Ltd (Tokyo, Japan) . Cyflumetofen has a significant controlling effect on mites on fruits, vegetables, flowers and other plants without cross‐resistance to existing acaricides, and is very safe to non‐target plants, mammals and aquatic organisms, both beneficial organisms and natural enemies . At present, the main cyflumetofen formulation on the market is a 20% cyflumetofen suspension, which is degraded to its de‐esterified form (AB‐1) for killing mites after the active ingredient has entered into them.…”
Section: Introductionmentioning
confidence: 99%